2018
DOI: 10.1007/s10126-018-9845-1
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Alternations in the Testes Related to the Sterility of Triploid Fish

Abstract: The knowledge of understanding the molecular traits of the sterile triploid fish is sparse. Herein, we analyzed the microRNA (miRNA) alternations in the testes of the sterile triploid fish produced by crossing the tetraploid fish with the diploid fish, compared with those of tetraploids and diploids used as the controls. A total of 136, 134, and 142 conserved miRNAs and 105, 112, and 119 novel miRNAs were identified in the diploid, triploid, and tetraploid fish, respectively. The genes targeted by the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…In land animals, miRNAs generally exhibit a negative regulatory effect on gene expression and are involved in a number of biological processes (Alvarezgarcia and Miska 2005;Carrington et al 2003;Xu et al 2003). Post-transcriptional regulatory mechanisms have been shown to play important roles in LC-PUFA biosynthesis and glycolipid metabolism, as well as growth, development, reproduction and immune function in teleosts (Gong et al 2015;Her et al 2011;Siddique et al 2016;Škugor et al 2014;Tao et al 2018;Zhang et al 2014;Zhu et al 2015). In rabbitfish, miR-17 was found to be involved in the regulation of LC-PUFA biosynthesis by targeting Δ4 fads2 (Zhang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In land animals, miRNAs generally exhibit a negative regulatory effect on gene expression and are involved in a number of biological processes (Alvarezgarcia and Miska 2005;Carrington et al 2003;Xu et al 2003). Post-transcriptional regulatory mechanisms have been shown to play important roles in LC-PUFA biosynthesis and glycolipid metabolism, as well as growth, development, reproduction and immune function in teleosts (Gong et al 2015;Her et al 2011;Siddique et al 2016;Škugor et al 2014;Tao et al 2018;Zhang et al 2014;Zhu et al 2015). In rabbitfish, miR-17 was found to be involved in the regulation of LC-PUFA biosynthesis by targeting Δ4 fads2 (Zhang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Higher expression of miR-33a and miR-135b in tilapia testis has been correlated with maturation of testis via regulation of insulin signalling pathway (Xiao et al 2014). Tao et al (2018) also observed the importance of miR-21, miR-22a, miR-99, miR-100, miR-101a and miR-146a in testicular development (Tables 2,3).…”
Section: Nile Tilapia (Oreochromis Niloticus)mentioning
confidence: 68%
“…Bizuayehu et al (2012) not only reported the expression of sex-biased miRNAs in Atlantic halibut but also demonstrated the mediation of miRNA regulation via signals from neuroendocrine system. Another study analysed the miRNA transcriptomes from fish at different ploidy levels to demonstrate the epigenetic regulation sterility in triploid cyprinids (Tao et al 2018). The discovery of novel miRNAs in teleost gonads further broadens the horizon for the exploration of their functions in reproductive control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also seemed to be one of the best normalizing miRNA candidates associated with spermatogenesis and embryogenesis [31]. miR-193a was upregulated in sterile triploid sh which might take part in sperm activity and testicular development by targeting functional genes [32]. miR-34b expression in asthenozoospermia group was also signi cantly lower compared to control group [20].…”
Section: Discussionmentioning
confidence: 99%